Pullout behaviour of geosynthetics in a recycled construction and demolition material – Effects of cyclic loading. (June 2020) - Vieira, Castorina S.; Ferreira, Fernanda B.; Pereira, Paulo M.; Lopes, Maria de Lurdes
Highlights: Feasibility of using non-selected C&D material as alternative backfill in reinforced soil structures. No previous studies have been reported on geosynthetic/C&D material interfaces under cyclic loading. Cyclic loading may reduce the post-cyclic pullout resistance depending on geosynthetic type. Abstract: In recent years, the use of construction and demolition (C&D) materials as alternative aggregates in geotechnical engineering applications, such as embankments, pavement subbase layers and geosynthetic-reinforced structures has raised increasing attention from researchers and practitioners worldwide. On the other hand, geosynthetics, particularly geogrids and high strength geotextiles, are used as a reinforcement material in some of those applications. When these infrastructures are subjected to repeated loadings (e.g. traffic, wave and seismic loads), the understanding of the interaction properties at the backfill-geosynthetic interfaces under cyclic loading conditions is of primary interest. This paper describes an experimental study carried out using a large-scale pullout test apparatus to assess the load-strain-displacement behaviour of two geosynthetics embedded in a recycled C&D material under cyclic and post-cyclic loading conditions. Test results show that cyclic loading can measurably reduce the post-cyclic pullout resistance of the geotextile (up to 15%), when compared to that obtained from the benchmark monotonic test. Conversely, the cyclic loading did not significantly influence the pullout resistance of the geogrid. The cumulative cyclic displacements over the length of the geosynthetics were found to increase with the load amplitude and the pre-cyclic pullout load level. Moreover, under identical test conditions, the accumulated cyclic deformations along the geotextile length consistently exceeded those for the geogrid, possibly due to the lower tensile stiffness of the geotextile at low strains.